A Promotive and Preventive Program for Febrile Seizures in Medan Barat District - Amelia, Putri; Lubis, Bastian; Akil, Muhammad (Talenta Publisher, 2021)
Febrile seizures are common neurological disorders in pediatric patients and usually affect children between 6 months and five years, peaking in 14 to 18 months. Mothers have a vital role in ensuring their family’s well-being. However, they often cannot contribute significantly to febrile seizure prevention and treatment at home due to the lack of knowledge and awareness. Therefore, we need to provide a promotive and preventive program for febrile seizures to the mothers at Medan Barat District, Medan, Sumatera Utara. This activity aims to reduce the incidence of febrile seizures in Indonesia. We delivered the program in several stages, from basic data collection, lectures, febrile seizure prevention, early management at-home training, evaluation, and guidebook handover. Twenty-nine people attended this program, twenty women (72.4%) and nine men (27.6%). No significant change was found in the level of knowledge and behavior before and after the activity (Z-score: 0,001; p= 1,000).